Proceedings of the 7th International Workshop on Evaluation and Usability of Programming Languages and Tools 2016
DOI: 10.1145/3001878.3001882
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative study of Java software buildability

Abstract: Researchers, students and practitioners often encounter a situation when the build process of a third-party software system fails. In this paper, we aim to confirm this observation present mainly as anecdotal evidence so far. Using a virtual environment simulating a programmer's one, we try to fully automatically build target archives from the source code of over 7,200 open source Java projects. We found that more than 38% of builds ended in failure. Build log analysis reveals the largest portion of errors are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 15 publications
2
25
0
4
Order By: Relevance
“…Recent work has shown that managing dependencies is a large and time consuming problem developers face when engaging in configuration management [18], [8], [19], [3], [9]. In particular, some developers have highlighted dependency management as one of the largest problems facing Python, requiring developers to spend non-trivial amounts of time on configuration for basic tasks.…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has shown that managing dependencies is a large and time consuming problem developers face when engaging in configuration management [18], [8], [19], [3], [9]. In particular, some developers have highlighted dependency management as one of the largest problems facing Python, requiring developers to spend non-trivial amounts of time on configuration for basic tasks.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Unfortunately, many code snippets require a non-trivial environment configuration in order to execute successfully [7], [8], and are not accompanied by sufficient information for developers to easily recreate that configuration [3], [9], [10]. This leads to the problem of configuration drift, where a code snippet goes out-of-date because the APIs that it depends on experience breaking changes over time.…”
Section: Introductionmentioning
confidence: 99%
“…Although in this paper we are focused on runtime information, the approach can be extended to map practically any machine-produced information to a piece of code -output from static analysis [25], build log messages [26], etc.…”
Section: Discussionmentioning
confidence: 99%
“…We focus the related work discussion in two areas: compilability [9,10,13,15,16,20] and software quality evolution [1,7,[17][18][19]22] by commit-level.…”
Section: Related Workmentioning
confidence: 99%